2000
DOI: 10.1093/gerona/55.7.m412
|View full text |Cite
|
Sign up to set email alerts
|

Medication Administration Hassles Reported by Family Caregivers of Dependent Elderly Persons

Abstract: Background. Even under the new long-term care mantra for increased home-and community-based care options, attention to and an understanding of the ways that family caregivers are managing complex care for dependent elderly persons, for example, with medication administration, have been slow to materialize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 14 publications
1
97
0
3
Order By: Relevance
“…These include the complexity of the process of medication management, the reporting of stress related to this caregiving role, strategies adopted by family caregivers as they manage medication and the lack of adequate medication management information and support available to family caregivers in this role (Travis et al 2000, Smith et al 2003, Cotrell et al 2006, Kaasalainen et al 2011. Importantly this current study highlights additional details of the experience of ethnic minority family caregivers in their medication management role caring for a person with dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the complexity of the process of medication management, the reporting of stress related to this caregiving role, strategies adopted by family caregivers as they manage medication and the lack of adequate medication management information and support available to family caregivers in this role (Travis et al 2000, Smith et al 2003, Cotrell et al 2006, Kaasalainen et al 2011. Importantly this current study highlights additional details of the experience of ethnic minority family caregivers in their medication management role caring for a person with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…While general studies of medication management by family caregivers of older adults are available (Travis, Bethea & Winn 2000;Smith et al 2003;Travis et al 2003;Francis, Smith, Gray & Denham 2006), few studies have focused exclusively on family caregivers of people living with dementia (Cotrell et al 2006, Kaasalainen et al 2011, While et al 2012. In particular, studies of the medication management experience of ethnic minority family …”
Section: Introductionmentioning
confidence: 99%
“…A administração de medicamentos é uma das tarefas mais complexas e frágeis do cuidado de um idoso (17), o que requer que os cuidadores demandem esforços múltiplos para garantia do uso correto e seguro da farmacoterapia. As alterações comportamentais, a falta de cooperação e compreensão do utente sobre o procedimento e os sintomas psiquiátricos, são aspectos que amplificam a resistência do idoso (15).…”
Section: "Estou Aqui Há Quatro Anos Mas Achava Que Não Iria Aguentarunclassified
“…15 A postal questionnaire study found that, if the questionnaire was completed by the stroke patient rather than a caregiver, this was associated with better persistence with medications. 16 In older adults with memory problems, it has been found that whether patients depend on themselves or a caregiver can have a significant impact on adherence.…”
Section: Factors Affecting Medication Adherence In Strokementioning
confidence: 99%